Pengaruh Modernisasi Sistem Administrasi, Motivasi, dan Kepercayaan Kepada Pemerintah terhadap Kepatuhan Pajak Bumi dan Bangunan: Studi Kasus pada Kecamatan Nogosari - Dira Nadian Salsabila; Yuwita Ariessa Pravasanti; Desy Nur Pratiwi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study examines the influence of modernization of the administrative system, motivation, and trust in the government on compliance in paying land and building tax (PBB-P2) in Nogosari District. The population in this study were land and building taxpayers. A sample of 100 respondents was taken using the Slovin formula. This study uses a quantitative approach with primary data collected through a questionnaire. Modernization of the administrative system (X1), motivation (X2), trust in the government (X3) and compliance in paying taxes (Y) are the variables used. In this study, the data were used for descriptive analysis, validity tests, reliability tests, and classical assumption tests. In addition, to test the hypothesis, multiple regression analysis was used for the f test, t test, and coefficient of determination (R2). All of this was done using the SPSS version 25 program. The results of the study, namely modernization of the administrative system (X1), motivation (X2), and trust in the government (X3), had a positive and significant impact on compliance in paying taxes (Y).